Teaching at Work
VIII, 268 p.
Keywords: This book presents a new and important scholarship on teaching, at the time when studies on teaching in teacher education are long overdue. This book is designed to put together such a set of chapters contributed by those teacher educators who are not only taking teaching as a professional practice, but also upholding teaching improvement as a scholarly pursuit that needs collaboration and systematic studies. Teaching at Work refers to not only the importance of effective teaching in K-12 classrooms and teacher preparation, but also the importance of taking teaching and its improvement as a subject of scholarly studies. In the field of teacher preparation, this book aims to make timely knowledge contribution and is positioned to stimulate further discussion and exploration on teaching and its improvement. The book contains 13 chapters by 35 scholars in the United States. This collection presents many innovative teaching practices and approaches as well as provides new insights into this topic of interest to teacher educators, researchers, and graduate students who wish to learn about various teaching approaches and practices for advancing teacher preparation.